ANALISIS LIFE CYCLE ASSESSMENT (LCA) “GATE TO GRAVE” PROSES PRODUKSI SEMEN - Aulia Ulfah Farahdiba; Nosa Syifa Yurinda (EnviroUS, 2022)
The cement production process of the Tuban Cement Plant until the use of cement products goes through several processes, namely quarry (mining), raw mill, pre heater, kiln & cooler, finish mill, packaging, and distribution (land transportation and shipping). Based on the activities carried out in cement manufacturing, it could have an impact on the environment. Therefore, it is necessary to conduct research related to the process and end of the product using Life Cycle Assessment (LCA) analysis. The scope of this analysis uses a gate to grave approach with SimaPro software. The largest impact categories from the results of this analysis are inorganic respiration, climate change and fossil fuel. Alternative environmental management as an improvement program that can be carried out are optimizing the use of bag filter maintenance, reducing the use of coal as fuel and replacing it with derivative fuels (RDF) and using biodiesel as fuel for distribution trucks.